2012
DOI: 10.1007/s10840-012-9670-9
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of atrioventricular nodal re-entrant tachycardia by cryoablation with an 8-mm-tip catheter versus radiofrequency ablation

Abstract: Compared to RF ablation, CRYO with an 8-mm-tip catheter for treating AVNRT achieves a comparable acute procedural success, comparably low recurrence rate and composite endpoint of treatment failure. Shorter fluoroscopy time and more energy applications were observed in the CRYO group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 23 publications
2
25
0
Order By: Relevance
“…The discrepancy may be explained by the fact that in the current study, the operator would stop fluoroscopy screening after the achievement of −70°C at the catheter tip during CRYO, whereas no such practice was emphasized in previous randomized studies. In a retrospective case‐control study, a similar observation of a reduction in fluoroscopic time in the CRYO group has been reported when the practice of minimization of fluoroscopy screening was adopted 7 …”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…The discrepancy may be explained by the fact that in the current study, the operator would stop fluoroscopy screening after the achievement of −70°C at the catheter tip during CRYO, whereas no such practice was emphasized in previous randomized studies. In a retrospective case‐control study, a similar observation of a reduction in fluoroscopic time in the CRYO group has been reported when the practice of minimization of fluoroscopy screening was adopted 7 …”
Section: Discussionsupporting
confidence: 54%
“…CRYO, with the phenomenon of cryoadhesion to enhance catheter stability and cryomapping to prevent inadvertent AVB, may reduce operator stress. On the other hand, cryoadhesion may also facilitate the reduction of fluoroscopic screening during ablation, as shown previously in a retrospective study 7 …”
Section: Introductionmentioning
confidence: 53%
“…Despite this, the long term recurrence rate appears to be acceptable at 8%. Other recent studies suggest that improved outcomes with cryoablation of AVNRT, perhaps comparable to radiofrequency ablation, may be achieved with 8 mm tip catheters [13], [14], linear ablation in the inferior portion of Koch's triangle [15], freeze-thaw-freeze cycles [16], and eliminating slow pathway conduction completely i.e. no jump or echo beats [17].…”
Section: Discussionmentioning
confidence: 99%
“…In a systematic review that combined 22 published studies (including 2654 patients), cryothermal ablation had a high procedural success rate (95%; range, 85%-99%) that was comparable with RFCA (95%-98%). [30][31][32][35][36][37][38][39][40][41][42][43][44][45][46][47] Long-term freedom from recurrent arrhythmia with cryoablation was reported to be 89% (range, 81.3%-98%), which was lower than historical observations with RF (3%-7% recurrence). 32 Although historical comparisons between observational studies are fraught with potential biases, 11 comparative studies between cryothermy and RFCA for AVNRT (8 retrospective observational studies and 3 prospective randomized studies; Table 1), reported comparable acute success rates.…”
Section: Av Nodal Reentrant Tachycardiamentioning
confidence: 99%
“…32 Although historical comparisons between observational studies are fraught with potential biases, 11 comparative studies between cryothermy and RFCA for AVNRT (8 retrospective observational studies and 3 prospective randomized studies; Table 1), reported comparable acute success rates. [36][37][38][39][40][41][42][43][44][45][46][47] Although the longer term recurrence rate was statistically similar in 7 of the 11 studies, there was an overall trend that favored RFCA. Procedural duration was globally similar, with a shorter fluoroscopy time with cryoablation.…”
Section: Av Nodal Reentrant Tachycardiamentioning
confidence: 99%